The effect of quorum sensing molecules on vascular function - Alassaf, Fawaz A. (2018)
Bacteria communicate with each other by releasing chemicals called quorum sensing molecules. A common gram-negative bacteria, Pseudomonas aeruginosa, releases a number of such molecules including, N-3-(oxododecanoyl)-L-homoserine lactone (3OC12-HSL) and Pseudomonas quinolone signal (2-heptyl-3,4-dihydroxyquinoline, PQS). The quorum sensing molecules have immunomodulatory effects on mammalian cells in addition to their role in bacteria. There has been very little study of the vascular effects of quorum sensing molecules on the host. The aim of this thesis was; therefore, to investigate the effect of Pseudomonas aeruginosa quorum sensing molecules, 3OC12-HSL and PQS, on vascular function and endothelial cell permeability and to study the potential mechanisms involved.